PERILAKU MENGUNDUH MP3 DI ERA GENERASI DOTCOM - Edi Priyono; - M. Nasir; - Chuzaimah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2011)
The online music service indicating, legal music, web sites is an innovative product, and it may causethe enormous change of procurement behavior of the music works. Like a lot of Asian countries, the onlinemusic market of Indonesia at present has just sprouted. The purpose of this paper is to provide an explanation offactors influencing online music purchase intention of Indonesian early adopter of online music, which can helpthe online music practitioners to develop better market strategies.The value of this paper is to establish a theoretical model incorporating the value-intention frameworkinto technology acceptance model to investigate the purchase behavior of early adopter of online music inIndonesia. The results of this study help online music practitioners to create a success business model.